Community dynamics of bottom-ice algae in Dease Strait of the Canadian Arctic. (December 2016) - Campbell, K.; Mundy, C.J.; Landy, J.C.; Delaforge, A.; Michel, C.; Rysgaard, S.
Highlights: Photosynthesis-irradiance (PI) parameters of ice algae measured using oxygen optodes in this study were not significantly different between thin (<10 cm) and thick (15–25 cm) snow covers. Light drives seasonal increases in maximum photosynthetic rate (in the absence of photoinhibition), the photoacclimation parameter and POC:chl a composition. Significant nutrient limitation in the study area of Dease Strait, Nunavut, limited algal production and caused high POC:PON ratios. Algal biomass and photophysiology were limited by both light and nutrients over a diel period. Abstract: Sea ice algae are a characteristic feature in ice-covered seas, contributing a significant fraction of the total primary production in many areas and providing a concentrated food source of high nutritional value to grazers in the spring. Algae respond to physical changes in the sea ice environment by modifying their cellular carbon, nitrogen and pigment content, and by adjusting their photophysiological characteristics. In this study we examined how the ratios of particulate organic carbon (POC) to nitrogen (PON), and POC to chlorophyll a (chl a ), responded to the evolving snow-covered sea ice environment near Cambridge Bay, Nunavut, during spring 2014. We also estimated photosynthesis-irradiance (PI) curves using oxygen-optodes and evaluated the resulting time-series of PI parameters under thin and thick snow-covered sites. There were no significant differences in PI parameters between samples from different overlying snow depths, and only the maximum photosynthetic rates in the absence of photoinhibition ( P s B ) and photoacclimation (IS ) parameters changed significantly over the spring bloom. Furthermore, we found that both these parameters increased over time in response to increasing percent transmission of photosynthetically active radiation (TPAR ) through the ice, indicating that light was a limiting factor of photosynthesis and was an important driver of temporal (over the spring) rather than spatial (between snow depths) variability in photophysiological response. However, we note that spatial variability in primary production was evident. Higher TPAR over the spring and under thin snow affected the composition of algae over both time and space, causing greater POC:chl a estimates in late spring and under thin snow cover. Nitrogen limitation was pronounced in this study, likely reducing P s B and algal photosynthetic rates, and increasing POC:PON ratios to over six times the Redfield average. Our results highlight the influence of both light and nutrients on ice algal biomass composition and photophysiology, and suggest a limitation by both resources over a diel period.